Impact of cell-free supernatant of lactic acid bacteria on Staphylococcus aureus biofilm and its metabolites - Mao, Yanni; Wang, Yuxia; Luo, Xiaofeng; Chen, Xiaohui; Wang, Guiqin (Frontiers in Veterinary Science, 2023)
Lactic acid bacteria (LAB), as a biocontrol agent, can inhibit the growth of pathogenic and food-spoilage bacteria. Its cell-free supernatant (LAB-CFS) is rich in bioactive substances. This manuscript examined the antimicrobial efficacy of LAB-CFS (both from planktonic and biofilm states) against the S. aureus biofilm state. Also, the LAB-CFS-mediated metabolomic alterations in biofilms and the changes in the expression of biofilms-associated genes in S. aureus were examined. LAB-CFS treatment significantly inhibited the bacterial growth, generation of eDNA (extracellular DNA), extracellular polysaccharides, and other physiological traits of S. aureus. Fluorescence microscopy revealed the negative impact of LAB-CFS on S. aureus biofilm. Moreover, LAB-CFS treatment reduced the expression of biofilm-associated genes. Metabolomic investigation revealed that LAB-CFS treatment had higher metabolites in biofilm-state than that in planktonic/monoculture systems, meanwhile, amino acid and nucleotide metabolic pathways were significantly altered. These findings imply that LAB-CFS has strong anti-S. aureus activity and exerts complicated bacterial interactions, both of which can be exploited as a novel therapy for mastitis.